Pemilihan Teknologi Sterilizer Pada Pabrik Kelapa Sawit Menggunakan Metode Analytical Hierarchy Process - Subiyanto, S (Department Industrial Engineering, University of Muhammadiyah Malang, 2013)
In Indonesia, the increasing area of palm oil plantation has been followed by the increasing number of palm oil mills from 205 units in 1998 to 695 units in 2012. The palm oil mill technology has also been developed, and one of them is fresh bunch sterilizer. The technology of sterilizer changed from horizontal to vertical, and the system improved from batch to continuous. This study analyze the determination of priority in selecting sterilizer technology by using Analytical Hierarchy Process (AHP) method. The advantages of AHP method are easy to understand and useful for decomposing a complex problems into a simple hierarchy of decision problem. According to the evaluation of three alternatives by using AHP, it shows that the priority order of the sterilizer models is respectively vertical, horizontal, and continuous with overall weight 0.366, 0.335, and 0.299 respectively.